Use of video-analysis feedback within a six-month coach education program at a professional football club - Wadsworth, N.; Charnock, L.; Russell, J.; Littlewood, M. (Journal of Sport Psychology in Action, 2020)
This research outlines how a neophyte sport psychology practitioner (SPP), working alongside a professional football coach, utilized video-analysis feedback within a six-month coach education program at an elite level professional football club. Video-analysis feedback was primarily utilized to improve the coach`s self-awareness in relation to his coaching practice. The intervention was also designed to support the integration of a psychosocial focus within the coaching context. Reflective accounts from both the neophyte SPP and the coach are provided. The reflections provide an insight into the efficacy of the intervention as well as presenting some of the challenges of delivering an intervention, such as this, within a professional football club. The use of video-analysis feedback provided the coach with an opportunity to reflect upon his coaching practice and as a result improve self-awareness of his coaching philosophy, especially in relation to the environment created within the coaching context and relationships developed with players.